Alveolar macrophages and airway hyperresponsiveness associated with respiratory syncytial virus infection - Wang, Yuxin; Zheng, Junwen; Wang, Xia; Yang, Pu; Zhao, Dongchi (Frontiers in Immunology, 2022)
Respiratory syncytial virus (RSV) is a ubiquitous pathogen of viral bronchiolitis and pneumonia in children younger than 2 years of age, which is closely associated with recurrent wheezing and airway hyperresponsiveness (AHR). Alveolar macrophages (AMs) located on the surface of the alveoli cavity are the important innate immune barrier in the respiratory tract. AMs are recognized as recruited airspace macrophages (RecAMs) and resident airspace macrophages (RAMs) based on their origins and roaming traits. AMs are polarized in the case of RSV infection, forming two macrophage phenotypes, termed as M1-like and M2-like macrophages. Both M1 macrophages and M2 macrophages are involved in modulation of inflammatory responses, among which M1 are capable of pro-inflammatory responses and M2 are capable of anti-proinflammatory responses and repaire damaged tissues in the acute and convalescent phases of RSV infection. Polarized AMs affect disease progression through alterating of immune cell surface phenotypes, participate in the regulation of T lymphocyte differentiation and the type of inflammatory response, which are closely associated with long-term AHR. In recent years, some progress has been made in the regulatory mechanism of AM polarization caused by RSV infection, which participates in acute respiratory inflammatory response and mediating AHR in infants. Here, we summarized the role of RSV-infection-mediated AMs’ polarization associated with AHR in infants.